Fifty years in home computing, the digital computer and its private use(er)s. Issue 2 (3rd March 2020) - Höltgen, Stefan
ABSTRACT: The following chapter will discuss the relation between home computer history and computer programming – with a focus on game programming. The nurseries of the early 1980s are the origins of the later computer game industry and the private use of microcomputers becomes an essential part of the 'playful' exploration and emancipation of technology. This is why the contribution that home computing added to the history of digital economics, culture and even thought cannot be estimated high enough. After the definition of central terms and discussing the main problems of the historiography of technology and computing, the main topic separated in decades will be portrayed. The milestones of home computer technology will be linked to the scenes and (sub)cultures of their users. Some of these links will be highlighted. My presentation will not be exhaustive but will try to highlight some of the playful uses of computers – from the perspective of this technology.